Tingkah Laku Bertelur Burung Maleo (Macrochepalon maleo S. Muller) di Taman Nasional Lore Lindu (TNLL) Blok Saluki - Fatmah Dhafir; Bustamin Bustamin; Isnainar Isnainar; Manap Trianto (Universitas Tadulako, 2022)
Knowledge of behavior is very important to maintain the habitat of the maleo as an endemic animal to Sulawesi that must be preserved. Research takes place in March-December 2021. The research location is in the Saluki Lore Lindu National Park, Central Sulawesi Province. The study took place in March-December 2021. The findings targeted in the study are: (1) Information on egg-laying behavior, (2). When laying eggs, (3) After laying eggs, (4) Determining the length of time for laying eggs, (5) Physical characteristics of the nest and vegetation. The research method used the survey method. Observations of maleo bird activity were carried out every day for 3 months in the egg-laying season from May to July. The results showed that the physical condition of the average nest depth was 67.78 cm, the average nest width was 52.78 cm, the average nest temperature was 33.44°C, the nest humidity was 76.11% and, the soil acidity (pH) with an average of 6.35. The vegetation found at the nesting site consisted of 18 species. The maleo maleo bird's egg-laying behavior activities are playing, snooping (observation), and making a trick hole. There were four activities of female maleo bird laying behavior, namely playing, digging holes for laying eggs, lurking, making trick holes and laying eggs. The duration of time needed by male maleo birds when playing, snooping, making holes, until the female finishes laying eggs, which takes 92 minutes. While the female takes 84 minutes.